Women’s Participation in Mangrove Conservation in Pantai Bahagia Village, Muara Gembong Regency, Bekasi - Messalina Lovenia Salampessy; Ina Lidiawati; Adriana Metak; Dewi Fitrianti (Green Insight Solutions, 2025)
Women’s participation in mangrove forest management is vital for effective planning policies, increasing women's empowerment, and better forest governance. Despite their central role in coastal livelihoods, women’s involvement in mangrove management remains poorly understood and often marginalized. This study aims to assess the roles of women and men in mangrove forest management and analyze the extent of women’s participation in Pantai Bahagia, Bekasi, Indonesia. The research employed qualitative methods, including in-depth and structured interviews, participant observation, and analysis using Arnstein’s Ladder of Citizen Participation. Data were collected from 54 respondents, comprising women from the KEBAYA group and key stakeholders, and analyzed using NVivo 11 for thematic coding. The results indicate that while women play essential roles in nursery and maintenance activities, their participation in planning, decision-making, and information access remains limited. Gender norms and socio-economic constraints, such as limited confidence, restricted mobility, and lower education levels, contribute to this disparity. Men remain dominant in decision-making and physically demanding tasks like planting. The study underscores the need for targeted interventions, including capacity-building programs, transparent information dissemination, inclusive decision-making forums, and strong multi-stakeholder partnerships. Enhancing women's participation in mangrove conservation could improve forest governance and contribute to more inclusive and sustainable resource management.